Second malignancies in patients with Hodgkin's Lymphoma: Half a century of experience. (July 2022) - Shbib Dabaja, Bouthaina; Boyce-Fappiano, David; Dong, Wenli; Damron, Ethan; Fang, Penny; Gunther, Jill; Rodriguez, Maria A.; Strati, Paolo; Steiner, Raphael; Nair, Ranjit; Lee, Hun; Abou Yehia, Zeinab; et al.
Abstract: Purpose: Therapeutic improvements for Hodgkin's Lymphoma (HL) has resulted in excellent survival outcomes. Thus, patients are increasing susceptible to developing secondary malignancy (SM) a feared iatrogenic complication. Materials & Methods: We evaluated the SM risk in a cohort of patients with HL treated over a 50-year period. In total, 1653 patients were treated for HL from 1956 to 2009 at a tertiary-cancer-center. A cumulative incidence function was used to quantify SM risk and the Fine and Gray competing risk model was used to identify disease and treatment related correlates. Results: Two-hundred-ninety patients (19%) developed SMs. Paradoxically, SM risk was higher in the modern era with 20-year cumulative incidence rates of 11.1%, 11.9%, 17% and 21.8%, for patients treated <1970, 1971–1986, 1986–1995 and 1996–2009, respectively. We hypothesized that the disproportionately high rate of early deaths in the early era may skew the assessment of SM risks, a much-delayed event. When the analysis was restricted to patients with early-stage favorable HL treated >1980, we found a reversal of the trend, especially on the risk of solid tumor, with a hazard ratio of 0.57 (p = 0.0651) in patients treated after 1996. Conclusion: Our findings highlight the limitations of comparing the risk of a late event between groups with disparate rates of early deaths, despite the use of a competing risk model. When partially corrected for, patients treated in the more recent time period experienced a lower solid tumor risk.